11B NMR Probes of Copper(II): Finding and Implications of the Cu2+‐Promoted Decomposition of ortho‐Carborane Derivatives. Issue 12 (21st March 2016) - Tanaka, Tomohiro; Nishiura, Yukiko; Araki, Rikita; Saido, Takaomi; Abe, Ryo; Aoki, Shin
Abstract: The development of noninvasive methodologies for the detection of d‐block metal ions such as copper (Cu 2+ ), zinc (Zn 2+ ), and manganese (Mn 2+ ) is important for understanding their biological roles and relationship with diseases. We have been interested in the use of 11 B NMR probes for the detection of d‐block metal ions, because 11 B is an ultratrace element in living systems. o ‐Carboranes, which consist of ten boron and two carbon atoms, have been applied to numerous drugs and biological active agents. In this work, we found that the o ‐carborane‐pendant cyclens (L 3 –L 5 ) (cyclen = 1, 4, 7, 10‐tetraazacyclododecane) are decomposed in the presence of Mn 2+ or Cu 2+ in aqueous solution at neutral pH, accompanied by the release of 4–9 equiv. of B(OH)3 . Furthermore, it was found that o ‐carborane derivatives that contain hydroxyl groups instead of a cyclen unit also undergo decomposition in the presence of Cu 2+ and the corresponding complexes such as Cu(bpy) to afford 10 equiv. of B(OH)3, as confirmed by 11 B NMR spectroscopic analysis and an azomethine‐H assay. These reactions are applied to 11 B MRI (magnetic resonance imaging) probes for Cu 2+ . Abstract : It is found that copper(II) ion promotes full decomposition reactions of o ‐carborane derivatives in aqueous solution to release 10 equiv. of B(OH)3 . The application of this discovery to 11 B NMR/MRI detection of Cu 2+ is also presented.